2001
DOI: 10.1523/jneurosci.21-04-01313.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Modulatory Inputs to Motor Networks: Early Established Projection and Progressive Neurotransmitter Acquisition

Abstract: Modulatory information plays a key role in the expression and the ontogeny of motor networks. Many developmental studies suggest that the acquisition of adult properties by immature networks involves their progressive innervation by modulatory input neurons. Using the stomatogastric nervous system of the European lobster Homarus gammarus, we show that contrary to this assumption, the known population of projection neurons to motor networks, as revealed by retrograde dye migration, is established early in embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…Thus, for the rest of this paper, Crust-MS effects refer to the effects of short-term bath application of Crust-MS. The PS neurons contain Crust-MS, but histamine is also present, as shown previously (Mulloney and Hall, 1991;Le Feuvre et al, 2001). We therefore examined the effects of a 3ms focal application of histamine to the STG and compared it with the modulation produced by Crust-MS application.…”
Section: Ps Stimulation Crust-ms Application and Focal Histamine Appmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, for the rest of this paper, Crust-MS effects refer to the effects of short-term bath application of Crust-MS. The PS neurons contain Crust-MS, but histamine is also present, as shown previously (Mulloney and Hall, 1991;Le Feuvre et al, 2001). We therefore examined the effects of a 3ms focal application of histamine to the STG and compared it with the modulation produced by Crust-MS application.…”
Section: Ps Stimulation Crust-ms Application and Focal Histamine Appmentioning
confidence: 76%
“…The pyloric suppressor (PS) neurons of homarid lobsters contain at least two co-transmitters: histamine (Mulloney and Hall, 1991;Le Feuvre et al, 2001) and an FMRFamide-like peptide (Fénelon et al, 1998). Their morphology is well characterized, with terminal endings in all four ganglia of the STNS [the oesophageal ganglion (OG), paired commissural ganglia (CoGs) and stomatogastric ganglion (STG)] (Meyrand et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, to contrast this situation with other neurohormones that are expressed during embryonic development, we have also included an analysis of RPCH and PDH, since these are also important neuromodulators. In view of the observations on expression of neuropeptides in the stomatogastric ganglion of lobsters, suggesting that some projection neurones do not express a 'peptide phenotype' until late in development (Le Feuvre et al, 2001), we considered our studies, which involve quantitative measurement of specific mRNAs in conjunction with neuroanatomical studies, to be especially relevant: Do transcript phenotypes mirror peptide expression? For MIH and CHH we observed significant expression of both mRNAs at the beginning of eye anlage formation, which rapidly increased during subsequent development.…”
Section: Discussionmentioning
confidence: 99%
“…Adult, larval, and embryonic STNS were dissected as described previously (Casasnovas and Meyrand, 1995;Le Feuvre et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that some of these modulatory GABAergic neurons, in addition to exogenous GABA, can exert important effects on the adult STNS networks (Cazalets et al, 1987;Nagy et al, 1994;Faumont, 1999;Meyrand et al, 2000;Swensen et al, 2000). A recent developmental study has shown that these modulatory neurons are present in the embryo but at least four of them do not express GABA at this developmental stage (Le Feuvre et al, 2001).…”
Section: Introductionmentioning
confidence: 99%